2011
DOI: 10.1348/096317910x508371
|View full text |Cite
|
Sign up to set email alerts
|

Job autonomy and workload as antecedents of workplace bullying: A two-wave test of Karasek's Job Demand Control Model for targets and perpetrators

Abstract: The current study aims to test the hypotheses that are central to Karasek's Job Demand Control Model in relation to workplace bullying. Particular contributions are, first, the focus upon both targets and perpetrators of workplace bullying, and second, the two‐wave design with a 6‐month time lag. We assume that (a) workload at Time 1 associates positively with being a target/perpetrator at Time 2, (b) job autonomy at Time 1 associates negatively with being a target/perpetrator at Time 2, and (c) the positive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
171
2
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(197 citation statements)
references
References 71 publications
11
171
2
13
Order By: Relevance
“…In line with previous studies in the field of bullying (e.g., Baillien, De Cuyper, & De Witte, 2011) all items were included in one scale. The scale showed adequate reliabilities at both waves (α = .84 and .87, respectively).…”
Section: Methodsmentioning
confidence: 94%
“…In line with previous studies in the field of bullying (e.g., Baillien, De Cuyper, & De Witte, 2011) all items were included in one scale. The scale showed adequate reliabilities at both waves (α = .84 and .87, respectively).…”
Section: Methodsmentioning
confidence: 94%
“…The moderating role of job autonomy in the leaderemember exchange (LMX) and service innovative behavior relationship Job autonomy is an important aspect of the job design framework (Baillien, De Cuyper, & De Witte, 2011;Karasek & Theorell, 1990). It is defined as " … the extent to which employees have a major say in scheduling their work, selecting the equipment they will use, and deciding on procedures to be followed" (Hackman & Lawler, 1971, p. 265).…”
Section: Leaderemember Exchange As a Mediator Between Ethical Leadersmentioning
confidence: 99%
“…However, only a few studies have been dedicated to work pressure and such studies found that work pressure is significantly and positively related to workplace bullying and aggression (Stouten et al, 2010;Baillien et al, 2011). On the bases of the above theoretical views and past empirical studies, we hypothesize thus:…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 92%